Exclusivity of Cultural Practices Within Emerging Disease Outbreak Responses in Developing Nations Leads to Detrimental Outcomes - Lal, Arnav (Frontiers in Public Health, 2021)
A number of organizations provide aid and medical care to areas affected by emerging infectious disease outbreaks. This process oftentimes involves organizations travelling to developing areas and coordinating efforts on-site of the initial outbreak. Yet, the longevity and death toll of specific recent outbreaks and inability to effectively control them leads to unnecessary deaths and an unconstructive use of resources. While virtually all organizations justifiably point towards limited resources as an explanatory mechanism, this in itself does not excuse poor utilization of resources. Specifically, organizations systematically do not factor cultural practices into their disease responses. This is demonstrated in analyzing components of responses during 3 recent outbreaks occurring at different times and on different continents: Ebola in 2014 and 2019, and Zika in 2016. While systemic trends in theses differential environments demonstrate the extent of the problem, fortunately, scientific innovations, collaboration with local individuals and leadership, and especially establishment of cross-cultural dialogue and response flexibility with the eventual development of effective behavioral change communication can help curb or mitigate this issue in the future.